PENGARUH LABA OPERASI, FREE CASH FLOW DAN STRUKTUR MODAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN AUTOMOTIVE YANG TERDAFTAR DI BEI PERIODE 2008-2012 - Ullya Tiza; Haryetti '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
In order to test the effect of multiple linear regression test was used. The purpose of this research is to determine the influence of each each independent variable on the dependent variable partially and simultaneously. Furthermore, to determine among the three independent variables in this study, which is the most dominant In order to test the effect of multiple linear regression test was used. The purpose of this research is to determine the influence of each each independent variable on the dependent variable partially and simultaneously. Furthermore, to determine among the three independent variables in this study, which is the most dominant influence dependent variable. Effect of operating profit (X1), free cash flow (X2) and capital structure (X3) partially on the company's dividend policy outomative ie 0.000000008202 for operating profit, 0.00000000002353 for 5208 free cash flow and capital structure, the constant value of 25 350. Determinant coefficient (R2) showed 0334. As a suggestion in this study (1) for potential investors before investing should seek out the company profile because it involves the performance of the company. (2) Investors should pay attention to operating profit and capital structure of the company who have a significant effect on dividend policy. (3) For further research is recommended to measure the influence of other variables besides how far the independent variables in this study.Keywords: Operating Profit, Free Cash Flow, Capital Structure Dividend Policy, Company Automotove